Classification of a new phytoplasmas subgroup 16SrII-W associated with Crotalaria witches’ broom diseases in Oman based on multigene sequence analysis - Al-Subhi, Ali (BMC Microbiol, 2017)
BACKGROUND: Crotalaria aegyptiaca, a low shrub is commonly observed in the sandy soils of wadis desert and is found throughout all regions in Oman. A survey for phytoplasma diseases was conducted. During a survey in a wild area in the northern regions of Oman in 2015, typical symptoms of phytoplasma infection were observed on C. aegyptiaca plants. The infected plants showed an excessive proliferation of their shoots and small leaves. RESULTS: The presence of phytoplasma in the phloem tissue of symptomatic C. aegyptiaca leaf samples was confirmed by using Transmission Electron Microscopy (TEM). In addition the extracted DNA from symptomatic C. aegyptiaca leaf samples and Orosius sp. leafhoppers were tested by PCR using phytoplasma specific primers for the 16S rDNA, secA, tuf and imp, and SAP11 genes. The PCR amplifications from all samples yielded the expected products, but not from asymptomatic plant samples. Sequence similarity and phylogenetic tree analyses of four genes (16S rDNA, secA, tuf and imp) showed that Crotalaria witches’ broom phytoplasmas from Oman is placed with the clade of Peanut WB (16SrII) close to Fava bean phyllody (16SrII-C), Cotton phyllody and phytoplasmas (16SrII-F), and Candidatus Phytoplasma aurantifolia’ (16SrII-B). However, the Crotalaria’s phytoplasma was in a separate sub-clade from all the other phytoplasmas belonging to Peanut WB group. The combination of specific primers for the SAP11 gene of 16SrII-A, −B, and -D subgroup pytoplasmas were tested against Crotalaria witches’ broom phytoplasmas and no PCR product was amplified, which suggests that the SAP11 of Crotalaria phytoplasma is different from the SAP11 of the other phytoplasmas. CONCLUSION: We propose to assign the Crotalaria witches’ broom from Oman in a new lineage 16SrII-W subgroup depending on the sequences analysis of 16S rRNA, secA, imp, tuf, and SAP11 genes. To our knowledge, this is the first report of phytoplasmas of the 16SrII group infecting C. aegyptiaca worldwide. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12866-017-1130-3) contains supplementary material, which is available to authorized users.